Composite substrate, manufacturing method and application
By constructing a composite substrate structure of a single crystal silicon substrate, polysilicon layer, silicon dioxide layer and piezoelectric thin film on silicon material, the problem that silicon material cannot be directly used in high-performance radio frequency acoustic surface wave devices is solved, and electrical performance is achieved The ability to stabilize and adapt to high-spec electrical components.
Patent Information
- Application Number
- CN202411232272.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-02-14
AI Technical Summary
Due to the symmetrical crystal structure of silicon materials, they cannot be directly used to prepare high-performance radio frequency acoustic surface wave devices, and the prior art is difficult to achieve stable electrical performance and adaptable to substrate wafers with high-specification electrical components.
A composite substrate structure with a single crystal silicon substrate, a polycrystalline silicon layer, a silicon dioxide layer and a piezoelectric thin film arranged in sequence is adopted. By controlling the thickness of each layer and the roughness of the contact surface, a stable multi-layer structure is formed to improve electrical performance. .
It realizes the stability of electrical performance and the ability to adapt to high-spec electrical components, while improving the mechanical strength and stability of the composite substrate, reducing stress and enhancing the reliability of the substrate.
Smart Images

Figure CN119451537A_ABST
Abstract
Description
[0001] This invention is a divisional application. The application number of the parent application is 202311077689.3, the application date is August 24, 2023, and the name of the invention is “Composite substrate, manufacturing method and application”. Technical Field
[0002] The present invention relates to the field of semiconductors, and in particular to a composite substrate with a multi-layer structure and a manufacturing method and application thereof. Background Art
[0003] At present, the processing technology of silicon materials is very mature, and it is also a semiconductor material with many industrial applications. Therefore, silicon materials have been widely used in electronic components. Since silicon materials themselves have a centrosymmetric crystal structure, silicon has no linear piezoelectric effect. Therefore, silicon materials cannot be directly used to prepare high-performance RF surface acoustic wave devices. The performance of RF surface acoustic wave devices such as SAW depends on the good piezoelectricity of the composite piezoelectric substrate. After the silicon material is converted into a silicon substrate with a grain structure, it can provide the performance of RF surface acoustic wave devices. Therefore, how to use silicon materials to obtain substrate wafers with stable electrical properties, adaptable to high-specification electrical components and high efficiency is an urgent problem to be solved. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a composite substrate, a manufacturing method and application thereof.
[0005] The first aspect of the present invention provides a composite substrate, comprising a single crystal silicon substrate, a polycrystalline silicon layer, a silicon dioxide layer and a piezoelectric film stacked in sequence; the thickness of the polycrystalline silicon layer is 0.05×λ to 3.0×λ, wherein λ is the main mode wavelength of the sound wave of the composite substrate; the thickness of the silicon dioxide layer is 0.05×λ to 1.0×λ.
[0006] According to an embodiment of the present invention, the single crystal silicon substrate is a crystal cut having Euler angles of (45°±10°, 54°±10°, 0°±10°).
[0007] According to another embodiment of the present invention, the contact surface between the single crystal silicon substrate and the polysilicon layer is a first contact surface, and the contact surface between the polysilicon layer and the silicon dioxide layer is a second contact surface; the roughness of the first contact surface and the roughness of the second contact surface are both less than 25nm.
[0008] According to another embodiment of the present invention, the roughness of the first contact surface and the roughness of the second contact surface are less than 15 nm and greater than 10 nm.
[0009] According to another embodiment of the present invention, the roughness of the first contact surface and the roughness of the second contact surface are both set to be less than 4 nm.
[0010] According to another embodiment of the present invention, the contact surface between the silicon dioxide layer and the piezoelectric film is a third contact surface, and the roughness of the third contact surface is less than 25 nm.
[0011] According to another embodiment of the present invention, the roughness of the third contact surface is less than 15 nm and greater than 10 nm.
[0012] According to another embodiment of the present invention, the roughness of the first contact surface, the roughness of the second contact surface and the roughness of the third contact surface are the same.
[0013] According to another embodiment of the present invention, the roughness of the first contact surface, the roughness of the second contact surface and the roughness of the third contact surface are different, and the roughness of the second contact surface is greater than the roughness of the first contact surface.
[0014] According to another embodiment of the present invention, the roughness of the third contact surface is smaller than the roughness of the second contact surface, and the roughness of the second contact surface is smaller than the roughness of the first contact surface.
[0015] A second aspect of the present invention provides a surface acoustic wave filter, comprising: the above-mentioned composite substrate;
[0016] An interdigital transducer is arranged on the surface of the composite substrate away from the single crystal silicon substrate, and includes a plurality of electrode fingers; wherein the interdigital transducer includes: a buffer layer, arranged on the piezoelectric film, the buffer layer includes metal titanium, and when the wavelength of the elastic wave determined by the electrode period of the IDT electrode of the interdigital transducer is set to λ, the thickness of the buffer layer is less than 0.5%λ; a metal layer, arranged on the surface of the buffer layer away from the piezoelectric layer, the metal layer includes aluminum, the thickness of the metal layer ranges from 1%λ-30%λ, the content of the aluminum is above 95wt%, and the metal layer also includes one or more materials selected from Cu, W, Mo, Cr, Ag, Pt, Ga, Nb, Ta, Au, and Si.
[0017] According to one embodiment of the present invention, the aluminum content of the metal layer is above 97 wt %.
[0018] According to another embodiment of the present invention, the titanium content of the buffer layer is above 98%, and the buffer layer further comprises one or more materials selected from Al, Si, and Mg.
[0019] According to another embodiment of the present invention, the average film thickness of the IDT is H, the acoustic wave wavelength responded by the SAW filter is λ, and the average film thickness H and the acoustic wave wavelength λ satisfy 8.5%≤H / λ≤12.5%.
[0020] According to another embodiment of the present invention, an average duty cycle of the IDT is greater than or equal to 0.4 and less than or equal to 0.8.
[0021] The third aspect of the present invention provides a method for manufacturing a composite substrate, comprising: S1, generating the polycrystalline silicon layer by deposition on the single crystal silicon substrate; S2, thermally oxidizing the surface of the polycrystalline silicon layer to form the silicon dioxide layer; and S3, bonding the piezoelectric film to the surface of the silicon dioxide layer to form the composite substrate having a multi-layer structure.
[0022] According to an embodiment of the present invention, in the step S1, the polysilicon layer is generated by physical deposition or chemical deposition.
[0023] According to another embodiment of the present invention, the physical deposition to generate the polysilicon layer comprises: controlling the energy of ion implantation to 2J / cm 2 -10J / cm 2 , a destructive area is formed in a preset range; polysilicon is produced through the destructive area.
[0024] According to another embodiment of the present invention, the chemical deposition to generate the polysilicon layer comprises: generating the polysilicon layer by vapor deposition in a silane gas atmosphere with a temperature controlled at 600-680° C. and a pressure of 0.3 Torr.
[0025] According to another embodiment of the present invention, the S3 step includes: performing ion implantation on the piezoelectric single crystal substrate to form an ion implantation area; transferring the piezoelectric thin film layer formed in the ion implantation area toward the surface of the multilayer structure formed in the S2 step; and annealing the transferred multilayer structure to form the composite substrate.
[0026] According to another embodiment of the present invention, the method further comprises: performing roughness treatment on the second contact surface and the third contact surface by laser annealing, and performing roughness treatment on the first contact surface by controlling ion implantation energy.
[0027] A fourth aspect of the present invention provides a radio frequency module, comprising one or more of a duplexer formed by the above-mentioned surface acoustic wave filter, a power amplifier, an antenna, a low noise amplifier, and a switch.
[0028] The composite substrate of the present invention utilizes silicon material to obtain stable electrical performance, and the composite substrate is suitable for high-specification electrical components and has high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a schematic diagram of a composite substrate according to one embodiment of the present invention.
[0030] Figure 2 It is a schematic diagram explaining the contact surface roughness in this article.
[0031] Figure 3 It is a schematic diagram of a surface acoustic wave filter according to one embodiment of the present invention.
[0032] Figure 4 It is a schematic flow chart of a method for manufacturing a composite substrate according to one embodiment of the present invention.
[0033] The reference numerals are described as follows:
[0034] 1-single crystal silicon substrate; 2-polycrystalline silicon layer; 3-silicon dioxide layer; 12-first contact surface; 23-second contact surface; 34-third contact surface; 4-piezoelectric film; 5-IDT electrode; 51-buffer layer; 52-metal layer DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with specific implementation modes.
[0036] like Figure 1 As shown, the composite substrate of the present invention includes a single crystal silicon substrate 1, a polycrystalline silicon layer 2, a silicon dioxide layer 3 and a piezoelectric film 4 which are stacked in sequence. In this way, a new composite substrate structure suitable for IHP-SAW with strong stability is formed. Among them, the use of polycrystalline silicon (Polycrystalline Silicon / poly-si) can achieve good electrical properties by giving priority to its high purity and high crystal quality. By forming a buffer layer on the silicon substrate layer by doping polycrystalline silicon, the lattice mismatch can be reduced, thereby improving the crystal quality of the wafer. Covering its surface with silicon dioxide can protect the surface of the wafer.
[0037] In the composite substrate, the bottommost single crystal silicon substrate 1 can also be replaced with glass. The single crystal silicon can be implemented as a crystal cut according to the following Euler angles: (0°±10°, 0°±10°, 45°±10°); or (45°±10°, 54°±10°, 0°±10°). Since the Euler angle of the crystal substrate material affects the preferred propagation direction of the acoustic mode in the selected substrate material, the crystal cutting angle of the single crystal silicon substrate is set as above to improve the signal propagation performance of the entire silicon-based composite substrate.
[0038] Furthermore, the polycrystalline silicon poly-si disposed on the single crystal silicon substrate 1 is also called polycrystalline silicon or polycrystalline silicon. The polysilicon layer 2 generally includes a plurality of silicon grains (crystals) (i.e., single crystal silicon grains) separated by grain boundaries, which can be randomly oriented and have different crystal orientations. It can serve as a supplement to the single crystal silicon substrate, improve the mechanical strength and stability of the wafer, reduce stress, and increase the reliability of the substrate. The thickness of the polysilicon layer 2 is preferably in the range of 0.05×λ to 13.0×λ, where λ is the wavelength of the main mode of the acoustic wave in the high acoustic velocity layer formed by the polysilicon layer, also referred to as the wavelength of the surface acoustic wave corresponding to the surface acoustic wave by the surface acoustic wave filter. Depending on the acoustic velocity in the high acoustic velocity layer, optimizing the thickness of the polysilicon layer 2 can produce the desired mode suppression to adapt to the high-specification device acoustic wave requirements. Considering the same effect, the silicon dioxide layer 3 is provided on the polysilicon layer 2. The thickness of the silicon dioxide layer 3 is in the range of 0.05×λ to 1.0×λ, thereby improving the compensation characteristics of the silicon dioxide layer 3. In addition, the silicon dioxide layer 3 can be a compound formed by adding fluorine, carbon, or boron to silicon dioxide.
[0039] In summary, the design of this structure aims to improve the mechanical strength and stability of the wafer, while improving the electrical performance of the wafer. Under the joint action of the single-crystal silicon substrate and the polycrystalline silicon layer, the mechanical strength and stability of the wafer are improved, the stress is reduced, and it is conducive to providing a high-performance composite substrate.
[0040] Continue to see Figure 1 Since the composite substrate of the present invention is a four-layer structure, there are three mutual contact surfaces, namely, the contact surface between the single crystal silicon substrate 1 and the polycrystalline silicon layer 2 is called the first contact surface 12, the contact surface between the polycrystalline silicon layer 2 and the silicon dioxide layer 3 is called the second contact surface 23, and the contact surface between the silicon dioxide layer 3 and the piezoelectric film 4 is called the third contact surface 34. The roughness of each contact surface in the composite substrate has a great influence on the performance of the formed device. In particular, the surface roughness of the single crystal silicon substrate 1 in contact with the polycrystalline silicon layer 2 is usually high, and the edge of its silicon wafer is very easy to produce large grains due to the influence of heat and nucleation mechanism when used with high-speed acoustic devices, thereby increasing power consumption and greatly affecting the performance of the product.
[0041] In this paper, the roughness of the contact surface refers to the distance between the lowest valleys of the two surface profiles within the sampling length, such as Figure 2 As shown, L is the roughness of the contact surface. In order to clearly show the contours of the two surfaces, Figure 2is an enlarged schematic diagram. Specifically, the roughness of the first contact surface 12 is the distance between the lowest valley of the profile of the surface of the single crystal silicon substrate 1 in contact with the polycrystalline silicon layer 2 and the lowest valley of the profile of the surface of the polycrystalline silicon layer 2 in contact with the single crystal silicon substrate 1. Similarly, the roughness of the second contact surface is the distance between the lowest valley of the profile of the surface of the polycrystalline silicon layer 2 in contact with the silicon dioxide layer 3 and the lowest valley of the profile of the surface of the silicon dioxide layer 3 in contact with the polycrystalline silicon layer 2. The roughness of the third contact surface is the distance between the lowest valley of the profile of the surface of the silicon dioxide layer 3 in contact with the piezoelectric film 4 and the lowest valley of the profile of the surface of the piezoelectric film 4 in contact with the silicon dioxide layer 3.
[0042] In this paper, the roughness of the contact surface can be measured by using AFM (atomic force microscope) to measure the roughness of the two surfaces, and then the roughness of the contact surface is obtained by adding the two. For example, the roughness of the surface where the single crystal silicon substrate 1 and the polycrystalline silicon layer 2 are in contact is Rz 11 , the roughness Rz of the surface where the polysilicon layer 2 contacts the single crystal silicon substrate 1 21 , then the roughness of the first contact surface Rz 12 =Rz 11 +Rz 21 By analogy, the roughness of the surface where the polysilicon layer 2 contacts the silicon dioxide layer 3 is Rz 22 The roughness of the surface where the silicon dioxide layer 3 contacts the polysilicon layer 2 is Rz 31 , then the roughness of the second contact surface Rz 23 =Rz 22 +Rz 31 The roughness of the surface of the silicon dioxide layer 3 in contact with the piezoelectric film 4 is Rz 32 The roughness of the surface where the piezoelectric film 4 contacts the silicon dioxide layer 3 is Rz 41 , then the roughness of the third contact surface Rz 34 =Rz 32 +Rz 41 The roughness of the first contact surface 12, the second contact surface 23 and the third contact surface 34 is set to be less than 25 nm. Under this roughness, the roughness can also be preferably greater than 10 nm and less than 15 nm. After many processing experiences, it can be concluded that within this roughness range, the unnecessary loss consumed by the reflection of sound waves can be reduced.
[0043] In addition, the roughness of the first contact surface 12 and the second contact surface 23 is set to a roughness range of less than 4 nm, so that the interface between the single crystal silicon substrate 1 and the polycrystalline silicon layer 2, and the polycrystalline silicon layer 2 and the silicon dioxide layer 3 can be more closely bonded to each other while ensuring the roughness requirements.
[0044] In an optional embodiment, the roughness of the first contact surface 12 , the second contact surface 23 , and the third contact surface 34 are the same.
[0045] In an optional embodiment, the roughness of the first contact surface 12, the second contact surface 23 and the third contact surface 34 are set to be different, and the roughness of the second contact surface 23 is greater than that of the first contact surface 12. This is conducive to achieving a higher response sound velocity of the polysilicon layer 2 than that of the silicon dioxide layer 3.
[0046] Thus, roughness parameters that meet high-performance devices can be flexibly set according to different device requirements. For example, the roughness of the third contact surface 34 can be smaller than that of the second contact surface 23 , and the roughness of the second contact surface 33 can be smaller than that of the first contact surface 12 .
[0047] On the basis of the above composite substrate, an IHP SAW device is formed, such as Figure 3 As shown, an interdigital transducer is arranged on the composite substrate. The interdigital transducer comprises an interdigital transducer electrode (IDT electrode), and the IDT electrode comprises a plurality of electrode fingers.
[0048] The interdigital transducer includes a buffer layer 51 disposed on a piezoelectric film 4 and a metal layer 52 disposed on the buffer layer 51. The buffer layer is metal titanium. When the wavelength of the elastic wave determined by the electrode period of the IDT electrode 5 is set to λ, the thickness of the buffer layer 51 is less than 0.5%λ. The metal layer 52 includes metal aluminum, and the content of the metal aluminum in the metal layer 52 is more than 95wt%, preferably more than 97wt%. The thickness of the metal layer 52 ranges from 1%λ to 30%λ.
[0049] The content of titanium in the buffer layer 51 is above 98wt%. Using metal titanium as the buffer layer 51 is conducive to forming a strong Al texture in the Al film of the metal layer 52 disposed thereon, enhancing the power bearing capacity of the Al film and reducing the resistivity of the Al film. Using a metal titanium layer with a thickness of 0.5%λ as the buffer layer 51 can improve the density and smoothness of the metal Al film, enhance the excitation of the surface acoustic wave, help reduce the insertion loss of the surface acoustic wave device, and help to increase the maximum withstand power of the SAW.
[0050] Exemplarily, when the wavelength λ of the elastic wave determined by the electrode period of the IDT electrode 5 is 2μm, the thickness of the buffer layer 51 is less than 10nm. In a preferred embodiment, the thickness of the buffer layer 51 can be set to 2nm, which can further enable the Al film subsequently formed thereon to obtain a strong texture. The thickness of the titanium buffer layer has a direct impact on the strength of the Al texture. After the titanium buffer layer is formed, the Al film thereon grows mainly in a layered mode. Al is a planar structure, and the Al surface is a low-energy surface, which has a tendency to grow preferentially. The Al film grown on the titanium buffer layer shows a strong texture. However, when the titanium buffer layer reaches a certain degree to form a continuous film, the deposition of the Al film on the titanium buffer layer begins to be mainly in an island growth mode, forming a polycrystalline structure without preferential orientation. Therefore, the thickness range of the titanium buffer layer that can promote the formation of Al texture is relatively narrow. The thickness of the titanium buffer layer is less than 10nm, preferably 2nm, and a strong Al texture can be obtained. The Al film obtained has a uniform and dense structure, an increased critical load, and significantly enhanced adhesion to the piezoelectric substrate.
[0051] Furthermore, the content of aluminum in the metal layer 52 is above 95wt%, and the metal layer 52 also includes one or more materials selected from Cu, W, Mo, Cr, Ag, Pt, Ga, Nb, Ta, Au, and Si. Doping in the aluminum metal layer can further improve the piezoelectric effect of the Al film. A small amount of doping elements can improve the anti-electromigration performance of Al, making the orientation of the Al film better. However, too high doping concentration will deteriorate the crystal quality of the Al film. The content of metal aluminum is above 97wt%, and the Al film with a small amount of doping materials has a good microstructure and surface morphology, so that the performance of the surface acoustic wave device is excellent and stable.
[0052] Furthermore, the aluminum content in the metal layer can be above 98%, and the buffer layer also includes one or more materials selected from Al, Si, and Mg. The purity of the metal titanium buffer layer has a great influence on the Al film subsequently formed thereon. When the metal titanium buffer layer is relatively thin (below 0.5%λ), the metal titanium buffer layer with higher purity is conducive to the formation of a strong texture of the metal Al film layer.
[0053] A titanium buffer layer 51 is formed between the Al metal layer 52 and the piezoelectric film 4, which improves the interface bonding strength between the IDT electrode 5 and the composite substrate, thereby avoiding the problem of the electrode finger vibrating more strongly and the electrode easily falling off from the substrate when the IHP SAW is used at high frequencies, causing the surface acoustic wave device to fail.
[0054] In an optional embodiment, the average film thickness of the IDT electrode 5 is H, the wavelength of the acoustic wave to which the series resonator responds is λ, and the average film thickness H and the wavelength of the acoustic wave λ satisfy 8.5%≤H / λ≤12.5%. The thickness of the IDT electrode 5 is linked to the wavelength of the acoustic wave to which the series resonator responds, thereby suppressing the frequency deviation of the surface acoustic wave filter, thereby reducing the insertion loss on the high-frequency side within the passband.
[0055] The average duty ratio of the IDT electrode 5 is defined as the ratio of the width of each of the plurality of electrode fingers to the sum of the width of each of the plurality of electrode fingers and the intervals between adjacent electrode fingers included in the plurality of electrode fingers. In an alternative embodiment, the average duty ratio of the IDT electrode 5 may be greater than or equal to 0.4 and less than or equal to 0.8.
[0056] The present invention also discloses a radio frequency module, comprising a duplexer formed by the above-mentioned IHP SAW, and one or more of a power amplifier, an antenna, a low noise amplifier, and a switch.
[0057] The composite substrate of the present invention can be Figure 4 It is made by following the steps shown in the figure. Figure 4 As shown, it includes: S1, generating a polysilicon layer 2 by deposition on a single crystal silicon substrate 1; S2, thermally oxidizing the surface of the polysilicon layer 2 to form a silicon dioxide layer 3; and S3, bonding a piezoelectric film 4 to the surface of the silicon dioxide layer 3 to form a composite substrate with a multi-layer structure.
[0058] In step S1, a single crystal silicon substrate is prepared, and polycrystalline silicon is produced on the single crystal silicon substrate. The polycrystalline silicon layer 2 can be formed by physical deposition or chemical deposition. Physical deposition can be, but is not limited to, sputtering to form the polycrystalline silicon layer 2. The polycrystalline silicon layer 2 can also be formed by chemical deposition, such as chemical vapor deposition, or other appropriate methods.
[0059] The polysilicon layer 2 is formed by sputtering. The single crystal silicon substrate 1 is cleaned to obtain a single crystal silicon substrate with a clean surface. The cleaning method can be to remove particles and contaminated metal impurities on the surface of the single crystal silicon substrate by wet chemical cleaning, so as to avoid the conductive factors on the surface causing subsequent device performance. Then, defects are formed on the single crystal silicon substrate 1 by ion implantation, and high doses of gases such as hydrogen, inert gas (such as H + or He + ) ions. Control the ion implantation energy to a fixed value, for example, the implantation energy can be adjusted from small to large ranges of 2 J / cm 2 -10 J / cm 2Thus, a certain destructive area is formed, thereby obtaining a polysilicon layer 2. At this stage, the current processing temperature is also controlled to be less than or equal to 1000° C. The polysilicon formed by such injection in a certain energy range can make the polysilicon layer 2 and the single crystal silicon substrate 1 integrally formed, thereby making the roughness between the two smaller than the roughness between the subsequent polysilicon layer 2 and the silicon dioxide layer 3 bonded.
[0060] The polysilicon layer 2 is formed by chemical vapor deposition, for example but not limited to, in a silane gas atmosphere with a temperature of 600-680° C. and a pressure of 0.3 Torr.
[0061] The polysilicon layer 2 can be formed in other embodiments by: preparing a trap-rich layer at the contact surface between the polysilicon layer and the single crystal silicon by ion implantation or by introducing a carbon-containing or nitrogen-containing gas, because the polysilicon layer is used to provide carrier traps and suppress the parasitic surface conductivity effect. The additional trap-rich layer added thereunder can prevent the trap density provided by the polysilicon layer from being insufficient. Compared with the polysilicon layer, the trap-rich layer can provide a greater defect density, enhance the capture of free carriers, and increase the resistivity of the substrate of the surface acoustic wave device. The thickness of the trap-rich layer can be 50nm to 200nm (in a certain proportional relationship with the polysilicon layer).
[0062] The thickness of the polysilicon layer 2 is preferably in the range of 0.05×λ to 13.0×λ during processing, where λ is the wavelength of the main mode of the acoustic wave in the high acoustic velocity layer formed by the polysilicon layer 2, also known as the wavelength of the surface acoustic wave corresponding to the surface acoustic wave by the surface acoustic wave filter. Depending on the acoustic velocity in the high acoustic velocity layer, the desired mode suppression can be produced by optimizing the thickness of the polysilicon to adapt to the high-specification device acoustic wave requirements.
[0063] In step S2, the surface of the polysilicon layer 2 is thermally oxidized to form a silicon dioxide layer 3. The oxidation time and oxidation temperature (for example, 650 to 800) for oxidizing the surface of the polysilicon layer 2 are controlled so that a silicon dioxide layer 3 with a high degree of fusion is formed on the surface of the polysilicon layer 2, thereby enhancing the adhesion between the polysilicon and the silicon dioxide and preventing it from falling off during use. Among them, the silicon dioxide layer 3 disposed on the polysilicon layer 2 is provided with a thickness range after oxidation, that is, the thickness of the silicon dioxide layer 3 is in the range of 0.05×λ to 1.0×λ, thereby improving the compensation characteristics of the silicon dioxide layer 3. In addition, during processing, fluorine, carbon or boron may be added to the silicon dioxide, so that the silicon dioxide layer contains the compounds formed thereby.
[0064] In step S3, the piezoelectric film 4 is bonded to the multilayer structure formed in step S2. A piezoelectric single crystal substrate is prepared in advance. The piezoelectric single crystal can be a crystal with piezoelectric function and photoelectric function, such as a lithium niobate crystal, a lithium tantalate crystal, a rubidium titanyl phosphate crystal, a potassium titanyl phosphate crystal, a silicon crystal, a germanium crystal or a gallium arsenide crystal. For example, a lithium niobate substrate can be used. A high dose of gas such as hydrogen, an inert gas (such as H + or He + ) ions, the original lithium niobate substrate can be adjusted to have a suitable tangent in advance, and the dose and energy of the ions during the implantation are adjusted according to the required film thickness. At this time, a damaged layer will be formed in the ion implantation area of the lithium niobate substrate, and the damaged layer is a piezoelectric film layer. It should be noted that the implanted ions are ions that can generate gas through heat treatment, such as hydrogen ions or helium ions. When hydrogen ions are implanted, the implantation dose can be 3×10 16 ions / cm 2 -8×10 16 ions / cm 2 The injection energy can be 120KeV-400KeV; when injecting helium ions, the injection dose can be 1×10 16 ions / cm 2 -1×10 17 ions / cm 2 The implantation energy can be 50KeV-1000KeV. The thickness of the thin film layer is adjusted by adjusting the ion implantation depth. Specifically, the greater the ion implantation depth, the greater the thickness of the prepared thin film layer; conversely, the smaller the ion implantation depth, the smaller the thickness of the prepared thin film layer.
[0065] Afterwards, the piezoelectric film layer formed in the ion implantation area of the lithium niobate substrate is transferred toward the multilayer structure formed in step S2. The specific transfer method can be: by molecular bonding to the multilayer structure formed in step S2, separation at the level of the piezoelectric film to transfer the surface layer of lithium niobate, i.e., the piezoelectric film layer, on the multilayer structure formed in step S2. Therefore, the overall structure can be solidified without damaging the quality of the transferred piezoelectric layer film or the mechanical strength of the heterostructure after the bonding is completed.
[0066] Finally, the transferred multilayer structure is annealed as a whole. During the annealing process, the H injected into the lithium niobate crystal + or He +Microbubbles are formed, and then these microbubbles are connected to form a piece, which makes the lithium niobate wafer peel along the damaged layer, and the excess lithium niobate will be automatically separated, and finally the lithium niobate single crystal film, that is, the piezoelectric film, is transferred to the multi-structure obtained in step S2, and the output film obtains a four-layer composite substrate structure. As a result, the uniformity of the obtained film is very good, the defect density is small, and no corrosive liquid is generated. After the hydrogen escapes, it is also non-toxic and harmless, there is no environmental pollution problem, and the original substrate material can be recycled.
[0067] The roughness between the various contact surfaces can be controlled by laser annealing. The polysilicon / silicon dioxide surface is treated. The temperature of the laser annealing process is, for example, controlled at above 1200 degrees Celsius; and the laser annealing process time is not less than 3ns. After high-temperature annealing, the surface roughness of the polysilicon / silicon dioxide is significantly improved. In addition, energy can be transferred in the form of related light radiation (i.e., laser irradiation or laser annealing), or the laser source can be controlled in pulse or continuous wave (CW) mode to shape and polarize the laser beam to heat the substrate more evenly. The medium emitting the laser can be different types of radiation that produce different wavelengths (e.g., gas lasers, solid lasers, dye lasers, diode lasers, etc.). By adding laser annealing to the process control formed by integrating single crystal silicon and polycrystalline silicon, that is, reprocessing the polysilicon surface or the silicon dioxide surface according to the roughness requirements, the roughness relationship between the different contact surfaces of the composite substrate can be met.
[0068] For example, in order to obtain a first contact surface with a set roughness value, the roughness can be controlled by forming a damaged layer by ion implantation. The roughness of the second contact surface and the third contact surface can be controlled to a set value by laser annealing, and the laser annealing parameters of the second contact surface and the third contact surface do not need to be set to the same value, as long as the roughness of the corresponding set value is obtained.
[0069] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A composite substrate, characterized in that: It includes a single crystal silicon substrate, a polycrystalline silicon layer, a silicon dioxide layer and a piezoelectric film which are stacked in sequence; The thickness of the polysilicon layer is 0.05×λ to 3.0×λ, wherein λ is the main mode wavelength of the acoustic wave of the composite substrate; the thickness of the silicon dioxide layer is 0.05×λ to 1.0×λ.
2. The composite substrate according to claim 1, characterized in that The single crystal silicon substrate is a crystal cut having Euler angles of (45°±10°, 54°±10°, 0°±10°).
3. The composite substrate according to claim 1, characterized in that The contact surface between the single crystal silicon substrate and the polysilicon layer is a first contact surface, and the contact surface between the polysilicon layer and the silicon dioxide layer is a second contact surface; the roughness of the first contact surface and the roughness of the second contact surface are both less than 25 nm.
4. The composite substrate according to claim 3, characterized in that The roughness of the first contact surface and the roughness of the second contact surface are less than 15 nm and greater than 10 nm.
5. The composite substrate according to claim 3, characterized in that The roughness of the first contact surface and the roughness of the second contact surface are both set to be less than 4 nm.
6. The composite substrate according to claim 3, characterized in that The contact surface between the silicon dioxide layer and the piezoelectric film is a third contact surface, and the roughness of the third contact surface is less than 25 nm.
7. The composite substrate according to claim 6, characterized in that The roughness of the third contact surface is less than 15 nm and greater than 10 nm.
8. The composite substrate according to claim 6, characterized in that The roughness of the first contact surface, the roughness of the second contact surface, and the roughness of the third contact surface are the same.
9. The composite substrate according to claim 6, characterized in that The roughness of the first contact surface, the roughness of the second contact surface, and the roughness of the third contact surface are different, and the roughness of the second contact surface is greater than the roughness of the first contact surface.
10. The composite substrate according to claim 6, characterized in that The roughness of the third contact surface is smaller than that of the second contact surface, and the roughness of the second contact surface is smaller than that of the first contact surface.
11. A surface acoustic wave filter, characterized in that: The invention comprises a composite substrate as claimed in any one of claims 1 to 10.
12. A method for manufacturing a composite substrate according to any one of claims 1 to 10, characterized in that: include: S1, generating the polycrystalline silicon layer on the single crystal silicon substrate by deposition; S2, thermally oxidizing the surface of the polysilicon layer to form the silicon dioxide layer; as well as S3, bonding the piezoelectric film to the surface of the silicon dioxide layer to form the composite substrate with a multi-layer structure.
13. The method for manufacturing a composite substrate according to claim 12, characterized in that: In the step S1, the polysilicon layer is generated by physical deposition or chemical deposition.
14. The method for manufacturing a composite substrate according to claim 13, characterized in that: The physical deposition to generate the polysilicon layer comprises: The energy of ion implantation is controlled to be 2J / cm 2 -10J / cm 2 , forming a destructive area within a preset range; Polycrystalline silicon is produced through the destructive region.
15. The method for manufacturing a composite substrate according to claim 13, characterized in that: The chemical deposition to generate the polysilicon layer includes: generating the polysilicon layer by vapor deposition in a silane gas atmosphere with a temperature controlled at 600-680° C. and a pressure of 0.3 Torr.
16. The method for manufacturing a composite substrate according to claim 12, characterized in that: The S3 step includes: Performing ion implantation on the piezoelectric single crystal substrate to form an ion implantation region; Transferring the piezoelectric film layer formed in the ion implantation area toward the surface of the multilayer structure formed in step S2; and The transferred multilayer structure is annealed to form the composite substrate.
17. The method for manufacturing a composite substrate according to any one of claims 12 to 16, characterized in that: The method further comprises: The second contact surface and the third contact surface are roughened by laser annealing, and the first contact surface is roughened by controlling ion implantation energy.
18. A radio frequency module, characterized in that: Comprising the composite substrate as described in any one of claims 1-10.